Management of Dyslipidaemia for the Prevention of Stroke: Clinical Practice Recommendations from the Lipid Association of India - Puri, Raman; Mehta, Vimal; Iyengar, Shamanna S.; Srivastava, Padma; Yusuf, Jamal; Pradhan, Akshaya; Pandian, Jeyaraj Durai; Sharma, Vijay K.; Renjen, Pushpendra Nath; Muruganathan, Arumugam; Krishnan, Mugundhan; Srinivasan, Avathvadi Venkatesan; et al. (Current Vascular Pharmacology, 2022)
Stroke is the second most common cause of death worldwide. The rates of stroke are increasing in less affluent countries predominantly because of a high prevalence of modifiable risk factors. The Lipid Association of India (LAI) has provided a risk stratification algorithm for patients with ischaemic stroke and recommended low density lipoprotein cholesterol (LDL-C) goals for those in very high risk group and extreme risk group (category A) of <50 mg/dl (1.3 mmol/l) while the LDL-C goal for extreme risk group (category B) is ≤30 mg/dl (0.8 mmol/l). High intensity statins are the first-line lipid lowering therapy. Nonstatin therapy like ezetimibe and proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors may be added as an adjunct to statins in patients who do not achieve LDL-C goals with statins alone. In acute ischaemic stroke, high intensity statin therapy improves neurological and functional outcomes regardless of thrombolytic therapy. Although conflicting data exist regarding increased risk of intracerebral haemorrhage (ICH) with statin use, the overall benefit risk ratio favors long-term statin therapy necessitating detailed discussion with the patient. Patients who have statins withdrawn while being on prior statin therapy at the time of acute ischaemic stroke have worse functional outcomes and increased mortality. LAI recommends that statins be continued in such patients. In patients presenting with ICH, statins should not be started in the acute phase but should be continued in patients who are already taking statins. ICH patients, once stable, need risk stratification for atherosclerotic cardiovascular disease (ASCVD).
Keywords: Stroke